Responsabilidade por vícios do produto e do serviço - Marcucci, Márcio (2007)
In regard to balance the relation between the quality of products and services offered in the market, and the value expended by the consumer to acquire those products and services, a detailed analysis is necessary about the juridical regime adopted in the consume relationships. The lawful model of civil responsibility is insufficient to attend to the demands of the current consumption society, which is extremely complex and characterised by vigorous industrialization, distribution and massive consumption of products and services. From this standpoint, the juridical regime of civil responsibility of the supplier for damages caused by defective products or services, named Responsibility by Accident Caused by Consumer is perfectly pertinent. For this reason, the study of this matter is essential. We aim to achieve practical solutions for addressing juridical problems and bring the academic debate about the Responsibility by Accident Caused by Consumers up. In the Brazilian laws, this new model of responsibility was brought up by the 12th and 17th articles of the Consumer s Defence Code, which addresses the responsibility of the retailer for the product and service, covering not only the legal right but also the contractual guarantee. We have intended to delimitate the developed matter exclusively regarding to responsibility for product and service vice, once there is a crossing over of several issues that gravitate around the matter of civil responsibility. This thesis begins with a short historic digression presentation aiming to provide a better understanding of the origins of civil responsibility and its evolution - bear in mind as well the development of the national law. The analysis of some topics of the Consumer s Defence Code will lead us to delimitate its fields of incidence, and will set the ambit of protection dedicated to whom its code if destined. We intended to define objectively the issues of major relevance for the understanding of our thesis, such as: responsibility, vice and defect, consumer and supplier, products and services, and so on. Aiming to the development of the subject, several doctrinaire standpoints were brought up and these allowed us to identify existing divergences and set our point of view. From jurisprudence, we have collected not only the fundamentals, but essentially the practical utilization of each discussed matter